Pneumococcal Vaccine Uptake in Adults Before and After Hospitalization for Pneumococcal Infections in Hong Kong, 2015 to 2024 - King-Pui Florence Chan; Ting-Fung Ma; James Chung-Man Ho; Ivan Fan-Ngai Hung; Mary Sau-Man Ip; Pak-Leung Ho (Vaccines)
Background/Objectives: Vaccination is a key preventive measure against pneumococcal disease, but uptake rates remain low in high-risk populations. Limited information exists on pneumococcal vaccine uptake in individuals with a history of pneumococcal disease. This study aims to assess pneumococcal vaccine uptake and the factors associated with it in patients hospitalized for pneumococcal disease, before and after hospitalization, across time periods before, during, and after the COVID-19 pandemic. Methods: Data for patients aged ≥18 years who were hospitalized for pneumococcal disease between 2015 and 2024 were extracted from the Hospital Authority’s territory-wide electronic medical record database. The uptake of pneumococcal vaccines in subgroups aged 18–64 years and ≥65 years, with and without risk conditions, both before and after hospitalization for pneumococcal disease, was assessed, followed by multivariate analyses of the factors associated with vaccination uptake by logistic regression models. Results: This study included 5517 patients hospitalized for pneumococcal disease. Prior to hospitalization, the vaccination uptake among the eligible patients was 20.5%, with only 8.1% fully vaccinated, despite the majority (87.9%) having previous hospitalizations (subgroup medians 3–9 times) or outpatient clinic visits (subgroup median 61–107 times). After discharge, during a median follow-up of 1.85 years, almost all the eligible patients (98.4%) received subsequent inpatient (subgroup medians 3–4 times) and outpatient (subgroup medians 21–28 times) care, but only 32.2% of the eligible patients received the vaccine. Factors associated with increased vaccine uptake post-discharge included age ≥75 years (OR 1.6), ≥10 subsequent hospitalizations (OR 2.1), and ≥10 subsequent clinic visits (OR 55.9). Vaccination rates within 12 months post-discharge were significantly lower in the patients hospitalized during the COVID-19 pandemic (3.5%) compared to the baseline (11.6%) and post-COVID-19 (6.6%) periods. Conclusions: The uptake of the pneumococcal vaccine before hospitalization for pneumococcal disease was low and continued to be suboptimal post-discharge. Numerous vaccination opportunities were missed in both the inpatient and outpatient settings. These findings indicate a need to improve vaccination strategies.